2018
DOI: 10.1200/jop.2017.027144
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Clinician Communication: American Society of Clinical Oncology Consensus Guideline Summary

Abstract: What communication skills and tasks can clinicians use to optimize the patient-clinician relationship, patient and clinician well-being, and family well-being? Target Population and AudienceClinicians who care for adults with cancer. MethodsAn expert panel was convened to develop clinical-practice guideline recommendations based on a systematic review of the medical literature and a formal consensus process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 7 publications
0
41
0
Order By: Relevance
“…Despite the challenges of research on quality of communication, the evidence of low clinician competence and the evidence that training is efficacious have led to a consensus of professional clinician and policy‐making organizations, led by the National Academy of Sciences, for widespread and mandatory communication skills training. A 2017 guideline published by the American Society of Clinical Oncology (ASCO), in addition, concluded that communication training should be provided to every oncologist and trainee. These recommendations and guidelines could reasonably be applied to every health professional involved in caring for the seriously ill.…”
Section: Evidence‐based Training Changes Communication Behaviors and mentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the challenges of research on quality of communication, the evidence of low clinician competence and the evidence that training is efficacious have led to a consensus of professional clinician and policy‐making organizations, led by the National Academy of Sciences, for widespread and mandatory communication skills training. A 2017 guideline published by the American Society of Clinical Oncology (ASCO), in addition, concluded that communication training should be provided to every oncologist and trainee. These recommendations and guidelines could reasonably be applied to every health professional involved in caring for the seriously ill.…”
Section: Evidence‐based Training Changes Communication Behaviors and mentioning
confidence: 99%
“…The ASCO published communication guidelines in 2017 that specifically addressed how clinicians should acquire communication skills . The ASCO guidelines note that “communication skills training should be based upon sound educational principles and include and emphasize skills practice and experiential learning using role‐play scenarios, direct observation of patient encounters, and other validated techniques.” Second, training “should foster practitioner self‐awareness and situational awareness related to emotions, attitudes and underlying beliefs that may affect communication.” Third, “facilitators of communication skills training should have sufficient training and experience” because distinctive pedagogical knowledge is required.…”
Section: Existing Recommendations and Barriers To Their Implementationmentioning
confidence: 99%
“…Nevertheless, strategies to support patient-clinician communication are important, but often missing elements of self-management education for patients with cancer [11]. Recent evidence surrounding the use of patient question prompt lists [21], individualized clinician communication training [22], and recommendations from patient-clinician communication clinical practice guidelines [23] may be used to guide the integration of communication coaching strategies into self-management interventions that target both patients and clinicians.…”
Section: Discussionmentioning
confidence: 99%
“…Differences in participant adherence to clinician recommendations was a crucial factor in self-reported ratings of symptom management satisfaction and symptom distress. Clinicians must use effective communication (eg, establish goals for care and conversations with patients, gain insight surrounding patient’s understanding of their condition, check for patient’s understanding of information provided) [23] and spend sufficient time with the patient to vigilantly assess patients’ self-reported symptoms as the most severe symptoms may not be the most bothersome. In addition, effective patient-clinician communication about symptom management may increase patient adherence to clinician recommendations.…”
Section: Discussionmentioning
confidence: 99%
“…5 More recently, a systematic review by the American Society of Clinical Oncology (with Walter F. Baile as the senior author) was published with more specific recommendations for communication training. 6 Recommendations 9.1 and 9.2 are as follows:…”
Section: Introductionmentioning
confidence: 99%